Identifikasi Ektoparasit Pada Ikan Patin (Pagasius sp) Di Unit Pembenihan Rakyat (UPR) Yosua Distrik Sentani Kabupaten Jayapura - Tatipata, K. P. Beatrix (STIPER Santo Thomas Aquinas Jayapura, 2023)
This study aims to identify the types of ectoparasites patin (Pangasius Sp.) in the UPR Yosua catfish cultivation pond, Jayapura Regency. Conducted in March through Mei 2023 at the Fish Disease Testing Laboratory of the Fish Quarantine Center, Quality Control and Safety of Jayapura Fishery Products in Sentani. This study uses 30 juvenile tilapia fish measuring 10-15 cm. Observations parasite carried out using a compound microscope and identification by using Kabata (1985). Of the samples tested some Dactylogyrus Sp was found to infect the gills of catfish (Pangasius Sp.), and Trichodina sp found in catfish mucus.